PENGEMBANGAN PROFESIONALISME GURU MELALUI PKG, PKB, DAN PPG (DALAM JABATAN DAN PRA JABATAN) - Wahyu Febriani, Elok; Nugroho, Puspo; Mufidah, Nisrinatul; Rahayu Aditya, Sukma (SIGNIFICANT : Journal Of Research And Multidisciplinary, 2024)
This research was conducted to determine the criteria for professionalism and process of increasing teacher performance professionalism through PKB (Continuous Professional Development), PKG (Teacher Performance Assessment), and PPG (Teacher Professional Education). This research uses a qualitative method through library research, which is a research method that describes in detail and in depth a topic in a natural context about what actually happened, by reviewing literature based on previous research. The analysis method is carried out by reducing data, displaying data and drawing conclusions. The research results show that as a professional worker, teacher must maintain and develop his competence and professionalism in carrying out his duties in educating students. Indonesian government has provided many program to increase teacher professionalism through the PKB, PKG, and PPG which have even been regulated in legislation regarding the implementation process. The implementation of the PKB, PKG and PPG programs is expected to help Indonesian teachers to achieve the goal of quality education.